Education for Better Governance: A Look at the Ongoing Cadre Political Education in China - Shucheng Hua (Adult Education Research Conference, 2002)
The cadre political education in China is essentially featured by the government’s efforts in transforming cadres’ ideology, morality, and work ethics in order to create a better social image of the Chinese cadres in the public, to improve the relationship between the cadres and the masses, and to accomplish better governance for the people.